EFFECT OF LIQUID ORGANIC FERTILIZER FROM MARKET WASTE AND RICE WASHING WATER ON THE GROWTH OF LAND KANGKUNG (Ipomoea raptans) - Arin Makasa; Orbanus Naharia (Indonesian Biodiversity Journal, 2023)
Some of Indonesia's agricultural countries produce many types of vegetables; for example, mustard greens, cabbage, spinach, kale, and so on are usually cultivated in Indonesia. Market waste and rice washing water can make liquid organic fertilizer (POC). This research was structured to know the effect of rice washing water on land kangkung plants' growth and the concentration required in one planting period. The research location is Maesa Unima housing, Tondano District, Minahasa Regency, North Sulawesi Province. This study uses quantitative methods with the implementation of experiments. Using the RAL technique or Completely Randomized Design totaling four treatments and each repeated seven times With liquid organic fertilizer (POC) using four treatments, namely: P0: Control (Using plain water), P1: POC with a concentration of 15%, P2: POC with a concentration of 30% and P3: POC with a concentration of 45% and the parameters measured were the growth of water spinach plants, namely: land kale plant height, number of land kale plants and leaf length on land kale plants. The results showed that rice washing water affected the growth of kale plants, namely plant height, number of leaves, and leaf length, and the required concentration was 45%. The research is due to the large amount of organic and household waste in the market, which can pollute the environment if not utilized